AKTUALISASI KEPEMIMPINAN KEPALA SEKOLAH DALAM IMPLEMENTASI SISTEM FULL DAY SCHOOL - Suryanti, Eny Wahyu; Widayanti, Febi Dwi (FKIP Universitas Wisnuwardhana, 2018)
The success of the school in implementing a full day school system is inseparable from the actualization of the headmaster leadership. One of the excellent programs initiated in Indonesia is a full day school system. This program is an alternative model of education which is a learning process with a full day system. The full day school system is a way to develop the talents and creativity of students. The purpose of this study is to determine the actualization of the headmaster leadership in the implementation of a full day school system at the Islamic Education Institution in Malang City at the elementary school level. This type of research is using a descriptive qualitative approach whose data is obtained from observation, interviews, and documentation. The results of this study indicate that the actualization of the headmaster leadership in the implementation of a full day school system at the Malang City Islamic Education Institute at the Elementary School level plays a role as the designer of a full day school system program; implementing a full day school system program; and supervisor of the full day school system program.Keywords: leadership, headmaster, full day school